PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DISERTAI TOPICAL REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 X KOTO SINGKARAK - Saputra, Yoke Hendri; Anggraini, Villia; Febriana, Rina (Pendidikan Matematika, 2013)
Research on background by the studentâs comprehension of mathematical concepts is low. The type of research is research experimental with design Â Â random trials on the subject. Population is all studentâs of class VIII that registration in the school year 2013/2014, while sample is student of class VIII B as experiment class and VIII C as control class. Instrument that use in research is final test in from of essays, with a reliability test 0,926. Based on result analysis data obtained by the average in learning of result student experiment calss that is 79,7 and control calss that is 66,95. From result of statistical test t obtained t cound = 2, 3244 and t table = 1,682, because t cound > t table, then hypothesis that proposed to accepted. So it was concluded about studenâs comprehension of mathematical concepts with the aplication of cooperative learning type student team achievement division (STAD) with topical review better than the studentâs comprehension of mathematical concepts with conventional learning in class VIII SMPN 3 X Koto Singkarak.